In vitro chloroquine resistance for Plasmodium vivax isolates from the Western Brazilian Amazon - Chehuan, Yonne F (BioMed Central, 2013)
BACKGROUND: Chloroquine (CQ) and primaquine (PQ) are still the drugs of choice to treat Plasmodium vivax malaria in many endemic areas, Brazil included. There is in vivo evidence for the P. vivax resistance to CQ in the Brazilian Amazon, where the increase in the proportion of P. vivax malaria parallels the increase of unusual clinical complications related to this species. In this study, in vitro CQ and mefloquine (MQ)-susceptibility of P. vivax isolates from the Western Brazilian Amazon was tested using the double-site enzyme-linked lactate dehydrogenase immunodetection (DELI) assay. METHODS: A total of 112 P. vivax isolates were tested in vitro for CQ-susceptibility and out of these 47 were also tested for MQ-susceptibility. The DELI assay was used to detect P. vivax growth at 48-hour short-term culture in isolates with ring stages ranging from 50 to %. Each isolate was tested in triplicate and geometric means of IC50’s was obtained. Nineteen isolates were genetically characterized for pvdhfr, pvmrp1, pvmdr1 and pvdhps candidate genes likely related to CQ resistance (10 with IC50<40 nM and 9 with IC50 >100 nM). RESULTS: Twelve out of 112 isolates were considered resistant to CQ, resulting in 10.7% (IC95% 5.0-16.4), while 3 out of 47 (6.4%; IC95% 0.0-12.8) were resistant to MQ. A discrete correlation was observed between IC50’s of CQ and MQ (Spearman=0.294; p=0.045). For pvdhps gene, a non-synonymous mutation was found at codon 382 (S→C) in 5/8 CQ-sensitive samples and 1/9 CQ-resistant samples (p=0.027). The other molecular markers were not associated to CQ-susceptibility. CONCLUSIONS: In vitro CQ-resistance estimated in this study, estimated by the DELI test, was very similar to that observed in clinical trials, suggesting that in vitro procedures developed by capable local laboratories are useful in the surveillance of CQ-resistance in the Amazon; concurrent Amazon P. vivax strains with both CQ and MQ resistance may be common; and a non-synonymous mutation at pvdhps codon 382 (S→C) was associated to in vitro susceptibility to CQ, needing further studies to be confirmed.